Integrated Management of Stem Rot of Sunflower (Helianthus annuus L.) Incited by Sclerotium rolfsii Sacc. - Sumi, Kavi; Tiameren Ao, N. (International Journal of Bio-resource and Stress Management, 2023)
Sunflower is an important oil seed crop all over the world and is also an important oilseed crop in Nagaland. The present investigation was an attempt to explore the possibilities and develop effective management of stem rot disease caused by Sclerotium rolfsii in sunflower (Helianthus annuus L.) through the use of bioagents and botanicals. In in vitro studies, 3 (three) bioagents viz., Trichoderma harzianum, Trichoderma viride and Trichoderma virens were tested following dual culture method where S. rolfsii was observed to be inhibited up to 61.8% , 58.5% and 56.4% respectively. Altogether 10 (ten) botanicals viz. Mimosa pudica, Azadirachta indica, Allium cepa, Curcuma aromatica, Zingiber officinale Roscoe, Duranta sp., Acmella oleracea, Jatropha curcas, Eucalyptus sp., and Allium sativum were also tested in in vitro using poison food technique. Among which Allium cepa bulb extract and Curcuma aromatica rhizome extract at 5% conc. inhibited the growth of S. rolfsii completely (100% ) followed by Zingiber officinale Roscoe, rhizome extract at 15% conc. with 82.6% mycelial growth reduction. Under field condition, seed treatment with T. harzianum @ 4 gm 10 ml-1 of water kg-1 of seed was found to be the best for management of stem rot of sunflower which resulted in lowest percentage plant mortality (5.62% ), highest percentage disease control (94.69% ), highest germination (77.65% ) and plant height (118.57 cm) accompanied by highest yield (567.30 g plot-1) respectively